Tomorrow's table organic farming, genetics, and the future of food - Ronald, Pamela C.; Adamchak, Raoul W., 1953- (New York ; Oxford : Oxford University Press, 2008)
Through dialogue with friends and family, the authors explore explore the use of GE agriculture and consumer concerns. They discuss the contents of their own largely organic pantry, what they choose to feed their children, and how they have developed a specific criteria for the use of GE in agriculture.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Food -- Biotechnology; Genetically modified foods; Organic farming; Genetic engineering